Peran Micro Teaching terhadap Peningkatan Kepribadian pada Mahasiswa Pendidikan Matematika - Hafsyah Hafsyah; Rustiani S; Suarti Djafar; Pratiwi Pujilestari Alam (Journal on Education, 2023)
This study aims to determine the role of micro teaching learning in the Mathematics Education study program at the University of Muhammadiyah Enrekang (UNIMEN) in improving the character or personality of students who have taken micro teaching courses. This type of research is ex-post facto with a qualitative approach. Respondents in this study were students of the UNIMEN Mathematics Education study program who had taken micro teaching courses and whose status was still active. Data collection techniques through observation, in-depth interviews, and presentation of documentation. Qualitative data analysis through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study show that micro eaching plays a positive role in improving the character or personality of students who have taken micro teaching courses. Through micro teaching activities, students not only gain knowledge and experience regarding teaching, but also gain character or personality improvement in it, namely having an attitude of discipline, responsibility, creativity, and independence.